The Influence of Electronic Word of Mouth on Purchase Intention of Somethinc Products in E-Commerce Marketplace Category - Wardhani, Nugrahani Puspa; Roostika, Ratna (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The rapid growth of e-commerce and digital marketing has significantly influenced consumer purchasing decisions, particularly through Electronic Word of Mouth (eWOM). This study examines the impact of Information Credibility, Information Usefulness, Information Adoption, and Attitude Towards Information on Purchase Intention of Somethinc products in e-commerce marketplace platforms. Using a quantitative approach, data were collected through an online survey with convenience sampling, involving respondents who are active marketplace users and familiar with Somethinc. The study employed Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software for data analysis. The findings indicate that Information Credibility significantly influences both Information Usefulness and Information Adoption, suggesting that credible eWOM enhances consumer decision-making processes. Moreover, Information Adoption and Attitude Towards Information positively affect Purchase Intention, emphasizing the role of consumer perception in driving purchases. However, Information Usefulness does not have a direct impact on Purchase Intention, implying that the mere usefulness of information does not necessarily translate into a purchase decision. These results reinforce the importance of trustworthy e WOM in shaping consumer behavior. Businesses should focus on enhancing review credibility, optimizing consumer engagement strategies, and leveraging influencer marketing to strengthen their digital marketing efforts. Future research should explore additional factors such as brand loyalty and perceived risk, as well as expand the study to other product categories.